IMPLEMENTASI MODEL PROBLEM BASED LEARNING (PBL) DALAM PEMBELAJARAN AKIDAH AKHLAK DI MTS MUHAMMADIYAH ALAMANDA KINALI PASAMAN BARAT - Elfia Rosa; Januar; Hamdi; Alimir (CV. KAMPUS AKADEMIK PUBLISING, 2023)
Abstract. This research is that the learning process is still centered on the teacher which makes the teaching and learning process passive and also the teacher only uses conventional models. This will have an impact on students' enthusiasm for learning to be low.